Modeling a Language for Embedded Systems in Timed Automata - Hune, Thomas S. (BRICS Report Series, 2000)
We present a compositional method for translating real-time programs into networks of timed automata. Programs are written in an assembly like real-time language and translated into models supported by the tool Uppaal. We have implemented the translation and give an example of its application on a simple control program for a car. Some properties of the behavior of the control program are verified using the generated model.